2023
DOI: 10.3390/toxics11070626
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E (α-Tocopherol) Does Not Ameliorate the Toxic Effect of Bisphenol S on the Metabolic Analytes and Pancreas Histoarchitecture of Diabetic Rats

Sheila I. Peña-Corona,
Dinorah Vargas-Estrada,
Juan I. Chávez-Corona
et al.

Abstract: This study investigated whether the coadministration of vitamin E (VitE) diminishes the harmful effects provoked by plasticizer bisphenol S (BPS) in the serum metabolites related to hepatic and renal metabolism, as well as the endocrine pancreatic function in diabetic male Wistar rats. Rats were divided into five groups (n = 5–6); the first group was healthy rats (Ctrl group). The other four groups were diabetic rats induced with 45 mg/kg bw of streptozotocin: Ctrl-D (diabetic control); VitE-D (100 mg/kg bw/d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 116 publications
2
0
0
Order By: Relevance
“…On the other hand, we reported that VitE produced a synergic harmful effect on diabetic rat pancreas morphology and serum metabolites related to hepatic and renal metabolism when administered with BPS [61]. We observed the same results in healthy rats in our laboratory (manuscript in progress).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, we reported that VitE produced a synergic harmful effect on diabetic rat pancreas morphology and serum metabolites related to hepatic and renal metabolism when administered with BPS [61]. We observed the same results in healthy rats in our laboratory (manuscript in progress).…”
Section: Discussionsupporting
confidence: 81%
“…Our results are consistent with the literature regarding the binding of bisphenols with the AR and ER (Figure 6). However, surprisingly, the VitE and BPS molecular docking results with ER suggest that VitE could interfere or act in combination with BPS and provoke an additive or synergic effect with bisphenol, as we reported [61].…”
Section: Discussionsupporting
confidence: 48%